Analytical Study of the Implementation of Islamic Corporate Governance at Bank Syariah Indonesia Jailolo - Sudimram, Muh. Sajjaj; Sarafuddin, Putri Yani; Magasing, Diyana M. (STIE Amkop Makassar, 2025)
The purpose of the research is to examine the depth of the implementation of Islamic corporate governance at Bank Syariah Indonesia Jailolo. This research is a qualitative study using field research methods. The source of this research is primary data obtained through interviews with representative informants from the bank and secondary data collected through the bank's website www.bank.bsi.co.id. The research data collection techniques used are observation, documentation, and semi-structured interviews, and the data analysis technique used is data triangulation. The research results show that Bank Syariah Indonesia Jailolo consistently implements corporate governance based on Islamic corporate governance in accordance with applicable laws and regulations. In its operations, this bank adopts the principles of siddiq (openness), amanah (trust), tabligh (responsibility), tawazun (berkeadilan). Sharia compliance based on the values of the Qur'an and Hadith. These principles are implemented through policies that refer to the fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) to ensure that all aspects of the bank's management are in accordance with Islamic law, which does not contain elements of riba (interest), gharar (ambiguity), maysir (gambling), taghrir (deception), ikhtikar (monopoly), tadlis (deception of quality), and includes economic activities that are considered potentially harmful to customers.